Anti-cancer activity and immunoadjuvant properties of edible bird's nest extracts on human breast cancer cell line - Maruthai, M. Yoshiny S. (2019)
Edible Bird’s Nest (EBN) is well regarded as an immune enhancing nutraceutical food especially among the Chinese. Current cancer therapies bring adverse side effects, thus identification of a safe adjuvant medicine like EBN can provide a quality life for patients. Researches on the effect of EBN extract on the human breast cancer cell line (MCF-7) and human immune cells are still very limited. The aim of this study is to evaluate the anti-cancer activity and immunoadjuvant properties of EBN extract on MCF-7 cell line. Primarily, 3 types of EBN extracts coded as HMG, EHMG and pHMG were prepared using the water extraction method. These EBN extracts were then tested on their cytotoxicity level against MCF-7 and human immune cells (CD8+ and CD14+). Production of the key pro-apoptotic and anti-apoptotic molecules released in MCF-7, CD8+ and CD14+ cells before and after EBN treatment were measured through mRNA expression level, ELISA and Multiplex assay. Among the 3 EBN extracts, HMG showed the highest cytotoxic effect towards MCF-7 cells with IC50 of 15 ^g/mL. However, HMG showed no harm towards CD8+ and CD14+ cells with cell viability of more than 90%. qRT-PCR results for nonactivated and activated CD8+ and CD14+ cells showed increased of pro-apoptotic gene expression while lower anti-apoptotic gene expression after treated with HMG in single and co-culture. At the same time, supplementation of HMG increased the apoptosis through down regulation of anti-apoptotic genes and the up-regulation of pro-apoptotic genes in MCF-7 cells. Enhancement of pro-apoptotic and down regulation of anti-apoptotic soluble factors by non-activated and activated CD8+ and CD14+ cells in single and co-culture after treated with HMG also showed in ELISA and multiplex assay. In conclusion, the present study showed that HMG extract is a potential anti-cancer agent and causes no harm to human immune cells. qRT-PCR, ELISA and multiplex tests also verified that HMG acts as an immunoadjuvant by enhancing pro-apoptotic function in the human immune cells.